PEMISAHAN CESIUM DALAM PEB U3Si2/Al PASCA IRADIASI DENGAN METODE KOLOM PENUKAR KATION MENGGUNAKAN RESIN DOWEX - Nugroho, Arif; Anggraini, Dian; Boybul, Boybul; Indaryati, Sutri; Kriswarini, Rosika; Ginting, Aslina Br. (Urania: Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2024)
The burn up calculations of nuclear fuel by destruction method can be determined from the analysis of 137Cs isotope, as fission product. For this reason, the separation of 137Cs isotopes from uranium in irradiated fuel element plates of U3Si2/Al (PEB) needs to be done. The separation of 137Cs was done by using cation exchange column method with Dowex resin with weight variation of 1; 2; 3; 4; 5 and 6 g. This study aims to determine the content of 137Cs in irradiated fuel element plates of U3Si2/Al (PEB) using the cation exchange column method with Dowex resin to be compared with the result of 137Cs separation by cation exchange column method using Lampung zeolite and CsClO4 precipitation method. The irradiated fuel element plates of U3Si2/Al (PEB) PEB U3Si2/Al with a density of 2.96 gU/cm3 from the middle part of RI-SIE2 code and side plate 20 IDA 0045 was taken with weight 0.1103 g and dissolved with HCl 6N and HNO3 6N to obtain uranil nitrate solution. The U3Si2/Al post irradiated solution was 150 μL was added with 2 mL aquadest and added with Cs carrier 20 μL and 1 mL HCl 12 M. The solution mixture was used as feed into the anion exchange column (first column) containing the R-Cl resin –with the wight variation about 1; 2; 3; 4; 5 and 6 g. The effluent from the anion exchange column was introduced into the cation exchange column (second column) which contained R-NH4+ resin with weight variation of 1; 2; 3; 4; 5 and 6 g. The bounded 137Cs isotope in R-NH4+ resin in the column was being eluted using 1 M HCl of 15 mL and being vaporized until the volume reach ± 2 mL. The quantity of the 137Cs isotope in the effluent was measured by using a gamma spectrometer with a counting time of 500 s. The 137Cs isotope content in irradiated fuel element plates of U3Si2/Al with the density 2.96 gU/cm3is 0.000445 g/gPEB and the parameter of separation 137Cs with cation exchange column method using Dowex resin weighing 2 g with recovery is 98.67%. The result of separation of 137Cs by cation exchange column method is not much different from the result of separation 137Cs by cation exchange method and CsClO4 precipitation method. The 137Cs obtained can then be used for burn up calculations.